Effects of Bacterial Biofilm on Regulation of Neurovascular Unit Functions and Neuroinflammation of Patients with Ischemic Cerebral Stroke by Immunocyte: Effects of Bacterial Biofilm by Immunocyte - Wu, Yongsheng; Yang, Demin (Cellular and Molecular Biology, 2023)
In this experiment, the effects of biofilm on neurovascular unit functions and neuroinflammation of patients with ischemic cerebral stroke were investigated. For this purpose, 20 adult male rats were purchased from Taconic (8 to 10 weeks old, weighing between 20 and 24g) and selected as the research objects. Then, they were randomly divided into an experimental group (10 rats) and a control group (10 rats). Ischemic cerebral stroke rat models were established. Besides, pseudomonas aeruginosa (PAO1) was prepared manually and implanted into the bodies of rats in the experimental group. mNSS scores, cerebral infarction area, and the release of inflammatory cytokines of rats in the two groups were compared. Results showed that mNSS scores for rats in the experimental group at all periods were remarkably higher than those for rats in the control group (P<0.05), which demonstrated that the rats in the experimental group suffered much severer neurological impairment than those in the control group. In addition, the release of tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, inducible nitric oxide synthase (iNOS), and IL-10 were all higher than those of the control group (P<0.05). The cerebral infarction area of the experimental group at all periods was remarkably larger than that of the control group (P<0.05). In conclusion, the formation of biofilm led to the aggravation of neurological impairment and inflammatory reactions among patients with ischemic cerebral stroke.